2010
DOI: 10.1016/j.toxicon.2010.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Crotoxin: Novel activities for a classic β-neurotoxin

Abstract: Crotoxin, the main toxin of South American rattlesnake (Crotalus durissus terrificus) venom, was the first snake venom protein to be purified and crystallized. Crotoxin is a heterodimeric beta-neurotoxin that consists of a weakly toxic basic phospholipase A(2) and a non-enzymatic, non-toxic acidic component (crotapotin). The classic biological activities normally attributed to crotoxin include neurotoxicity, myotoxicity, nephrotoxicity and cardiotoxicity. However, numerous studies in recent years have shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0
22

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 157 publications
2
86
0
22
Order By: Relevance
“…Structurally, crotoxin is a heterodimeric β-neurotoxin that consists of a toxic basic phospholipase A 2 and a nonenzymatic, non-toxic acidic component (crotapotin). Crotapotin potentiates the activity of crotoxin, since it prevents the basic phospholipase subunit binding to non-specific sites (Sampaio et al, 2010;Soares et al, 2001). Crotoxin targets neuromuscular junctions and inhibits the release of acetylcholine, which leads to neuromuscular blockade and muscular and respiratory paralysis.…”
Section: Crotalus Venommentioning
confidence: 99%
See 1 more Smart Citation
“…Structurally, crotoxin is a heterodimeric β-neurotoxin that consists of a toxic basic phospholipase A 2 and a nonenzymatic, non-toxic acidic component (crotapotin). Crotapotin potentiates the activity of crotoxin, since it prevents the basic phospholipase subunit binding to non-specific sites (Sampaio et al, 2010;Soares et al, 2001). Crotoxin targets neuromuscular junctions and inhibits the release of acetylcholine, which leads to neuromuscular blockade and muscular and respiratory paralysis.…”
Section: Crotalus Venommentioning
confidence: 99%
“…Crotoxin targets neuromuscular junctions and inhibits the release of acetylcholine, which leads to neuromuscular blockade and muscular and respiratory paralysis. In the muscle tissue, crotoxin causes selective injury of skeletal muscle groups composed of type I and IIa fibers, which are extremely vascularized and rich in myoglobin (Sampaio et al, 2010). Other important toxins are crotamine, convulxin and gyroxin.…”
Section: Crotalus Venommentioning
confidence: 99%
“…Crotoxin was the first protein isolated and crystallized from animal venom [1,2]. a Crotoxin is a heterodimeric protein that consists of a non-toxic, nonenzymatic, acidic subunit (crotapotin, crotoxin A, CA) non-covalently associated with a weakly toxic, basic subunit (crotoxin B, CB) that expresses phospholipase A 2 activity.…”
Section: Introductionmentioning
confidence: 99%
“…Along with these well-known activities, several other biochemical and pharmacological effects have been reported, some of them highlighting the potential pharmaceutical use of this protein. These effects include the antibacterial, antiviral, anti-inflammatory, antitumoral, and analgesic activities of CTX and its subunits (CA and CB) [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Crotalus durissus neurotoxin (crotoxin) is a nerve toxin isolated from South American diamondback snake subfamilies. Recent studies have indicated a potential antitumor effect of crotoxin [6,7] , although its specific mechanism remains unclear. In this study, we therefore investigated the antitumor effects of crotoxin in human esophageal carcinoma (Eca-109) cells and in a nude mouse tumor transplantation model.…”
Section: Introductionmentioning
confidence: 99%